Kemampuan Konsentrasi Berhubungan dengan Waktu Reaksi tetapi Tidak Berhubungan dengan Pola Tidur di Pondok Pesantren - Handayani -; Herdiantri Sufriyana; Abraham Ahmad Ali Firdaus (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Pesantren as dormitory-based educational institutions familiarize their students with sleep patterns and certain activities, including sports that increase reaction time. This study aims to prove the relationship between sleep patterns and reaction time with the ability of concentration in adolescent girls. This cross-sectional study was conducted on 27 Wachid Hasyim boarding school students whose average age was 17.49 years (IK 95% 17.33-17,66). Subjects filled out the Pittsburgh Sleep Quality Index (PSQI) and Krawietz Concentration Scale (KCS) questionnaires and underwent the Ruler Drop Test. All three consecutively measured sleep patterns, concentration ability and reaction time. The KCS questionnaire assessed four components: 1) Control of Focus (CF); 2) Uncontrolled Focus (UF); 3) Reading and Listening Focus (RLF); And 4) Control of Focus Before Sleep (CFBS). The results show that the subject has a PSQI score of 6.41 (95% IK 5.29-7.52) that exceeds the normal limit. However, subjects had a rapid reaction time (55.6%) and a KCS score of 216.78 (95% IO 958.06-225.49; p = 0.044) higher than their mean value. There was no relationship between sleep patterns with concentration ability (p = 0.487). There is a negative correlation trend between sleep patterns and CFBS (r = -322; p = 0.050) or with reaction time (r = -394; p = 0.069). There was a relationship between reaction time and overall concentration (p = 0.048) and partially on RLF + CFBS (p = 0.029). There is a positive correlation between the reaction time in the form of the catch distance response with CFBS (r = 0.326; p = 0.049). The effort of pesantren in maximizing the use of time that caused poor sleep pattern was found did not decrease the ability of student concentration. Exercise that increases reaction time is found to reduce their ability to start sleeping